Glomerular C4d deposition in proliferative glomerular diseases - Sarojini Raman; Pallavi Mishra; Ansuman Panigrahi; Nikunj K Rout; Kanakalata Dash (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this study was to evaluate the immunohistochemical expression of C4d in native renal biopsies of proliferative glomerular diseases, complement pathways in these diseases, and assess the relationship of C4d with histological and clinicopathological parameters, other complement proteins, and immunoglobulin markers. Methods: This cross-sectional study was conducted during the year 2018-19 involving 107 native renal biopsies with histologically diagnosed cases of proliferative glomerular diseases. C4d immunohistochemical evaluation of renal tissue sections was performed using polyclonal antihuman C4d as the primary antibody. Patients were classified as positive and negative groups based on their glomerular C4d deposition. Results: The overall prevalence of C4d positivity was 80.4% in proliferative glomerular diseases ranging between 60.0% in C3 glomerulonephritis to 92.9% in membranoproliferative glomerulonephritis. Mixed capillary and mesangial deposition were noted in all cases of proliferative glomerulonephritis. Classical pathway was dominantly involved in all glomerular diseases except C3 glomerulonephritis and IgA nephropathy. Multivariate logistic regression analysis revealed that glomerular IgG staining (aOR: 5.86, 95% CI: 1.26-27.14) and IgM staining (aOR: 3.90, 95%CI: 1.07-14.18) were significantly associated with C4d positivity. Conclusion: C4d staining along with immunoglobulin markers such as IgG and IgM and complement proteins can be useful in delineating different complement activation pathways in glomerular diseases and understanding the disease pathogenesis.